Polemické spisy luterských ortodoxů jako reakce na konverzi Jana Zikmunda Braniborského - Anna Kancírová (Theatrum Historiae)
The study deals with the polemical texts of Lutheran Orthodox Theologians, who responded to the conversion of Johann Sigismund von Brandenburg to Calvinism (1613/1614). In the texts they criticized the Brandenburg court preacher Salomon Finck and strived to prevent the expansion of Calvinism in Brandenburg.